Experimental Validation of Designs for Permeable Diffractive Lenses Based on Photon Sieves for the Sensing of Running Fluids - Veronica Pastor-Villarrubia; Angela Soria-Garcia; Joaquin Andres-Porras; Jesus del Hoyo; Mahmoud H. Elshorbagy; Luis Miguel Sanchez-Brea; Javier Alda (Photonics)
This study reports the experimental validation of several designs of photon sieves with focusing capabilities. These permeable optical elements were implemented with a spatial light modulator working in pure-amplitude mode. The focal region was scanned using a traveling stage, holding a camera. Using this experimental setup, we characterized the focal region of the photon sieves and determined some parameters of interest, such as the depth of focus and the transverse extent of the focal region. These parameters and their evolution were measured and analyzed to compare the optical performance of different designs. Moreover, the permeability of the mask was also evaluated and is included in the discussion. When the photon sieve is intended to be used as an optical element for the monitoring of running fluids, one of the designs studied, labeled the Ring-by-Ring method, behaves in a quite balanced manner and thus has become the preferred choice. Through simulations for a refractometric sensor, we obtained the Figure of Merit of the Ring-by-Ring mask, which reached a maximum value of 7860 RIU−1, which is competitive with plasmonic sensing devices.